ABOUT THE NEED OF CREATING ELECTRONIC EDUCATIONAL DICTIONARIES FOR PRIMARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2023)
This article describes educational dictionaries, their role in the development of the intellectual potential of students, increasing vocabulary, developing thinking, mastering the existing literary norms of the language, developing competencies for the practical use of the language, and also discusses the creation of educational dictionaries that contribute to the interconnectedness of research on the compilation of dictionaries of a new generation and intended for primary school students.